2013
DOI: 10.1002/macp.201300322
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Ammonium and Phosphonium Polymerized Ionic Liquids: Thermal Analysis, Conductivity, and Morphology

Abstract: Conventional free radical polymerization and anion metathesis of ammonium and phosphonium styrenics successfully generates high‐molecular‐weight polymerized ionic liquids (PILs). Phosphonium polyelectrolytes containing Cl‐ counterions display significantly higher thermal stabilities (>370 °C) compared with ammonium analogs (<220 °C). Anion exchange to BF4–, TfO–, and Tf2N– improves the thermal stability of all the PILs and depresses their Tg. Impedance‐spectroscopy‐probed ionic conductivities of PILs containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
99
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 48 publications
3
99
0
Order By: Relevance
“…Compared with traditional organic frameworks, ionic hypercrosslinked polymers, specifically those involving ionic liquids as monomers, have attracted growing attention. These materials can possess good thermal and chemical stability, properties that can be tuned upon simple counterion exchange, and which can readily form layer‐by‐layer self‐assembled films with other ionic polymers . For example, Yang et al reported an alkaline anion exchange membrane R1 (Scheme ) comprised of copolymerized imidazolium‐functionalized ionic liquids with styrene and acrylonitrile.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional organic frameworks, ionic hypercrosslinked polymers, specifically those involving ionic liquids as monomers, have attracted growing attention. These materials can possess good thermal and chemical stability, properties that can be tuned upon simple counterion exchange, and which can readily form layer‐by‐layer self‐assembled films with other ionic polymers . For example, Yang et al reported an alkaline anion exchange membrane R1 (Scheme ) comprised of copolymerized imidazolium‐functionalized ionic liquids with styrene and acrylonitrile.…”
Section: Introductionmentioning
confidence: 99%
“…Long and co‐workers have recently reviewed several synthetic approaches towards phosphonium PILs, the majority of which involved the polymerization of vinylbenzylphosphonium monomers . In a prototypical example, Hemp et al reported a series of PILs where an increase in T d5% (temperature at which 5% of the PIL had decomposed) of 100–200 °C occurred when the cation was changed from ammonium to phosphonium across a wide range of counteranions (Cl, BF 4 , OTf, NTf 2 ) . An increase in ionic conductivity (log σ ) of up to an order of magnitude was also observed for the phosphonium PILs.…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few examples of phosphonium aprotic poly(ionic liquids) which are showing excellent properties. For example, Hemp et al synthesized poly(ionic liquids) composed of aprotic phosphonium cations . The polymers were used as nonviral gene delivery agents and compared with ammonium analogs showing enhanced DNA binding with better transfection efficiencies.…”
Section: Introductionmentioning
confidence: 99%